Soft S-Paracompact Space - Kumasi, Vishwanath; Thankachan, Baiju (IndoMS, 2025)
This paper introduces a new topological class called soft S-paracompact spaces. These spaces generalize the concept of soft paracompact spaces. A soft topological space is considered soft S-paracompact if every soft open cover has a locally finite soft semi-open refinement. We explore the key properties of soft S-paracompact spaces and investigate their relationships with other well-established soft topological spaces. We depict an application of soft S-paracompactness in the decision-making problem.